Expression profiling of winged‐ and wingless‐destined pea aphid embryos implicates insulin/insulin growth factor signaling in morph differences. Issue 3 (4th November 2019) - Grantham, Mary E.; Shingleton, Alexander W.; Dudley, Emma; Brisson, Jennifer A.
Abstract: Developmental plasticity allows the matching of adult phenotypes to different environments. Although considerable effort has gone into understanding the evolution and ecology of plasticity, less is known about its developmental genetic basis. We focused on the pea aphid wing polyphenism, in which high‐ or low‐density environments cause viviparous aphid mothers to produce winged or wingless offspring, respectively. Maternally provided ecdysone signals to embryos to be winged or wingless, but it is unknown how embryos respond to that signal. We used transcriptional profiling to investigate the gene expression state of winged‐destined (WD) and wingless‐destined (WLD) embryos at two developmental stages. We found that embryos differed in a small number of genes, and that gene sets were enriched for the insulin‐signaling portion of the FoxO pathway. To look for a global signature of insulin signaling, we examined the size and stage of WD and WLD embryos but found no differences. These data suggest the hypothesis that FoxO signaling is important for morph development in a tissue‐specific manner. We posit that maternally supplied ecdysone affects embryonic FoxO signaling, which ultimately plays a role in alternative morph development. Our study is one of an increasing number that implicate insulin signaling in the generation of alternative environmentally induced morphologies. Abstract : Hypothesized model linking ecdysone and insulin signaling in the pea aphid wing polyphenism. In mothers that are at low densities, ecdysone signaling is inferred to be low (Vellichirammal et al., 2016; Vellichirammal et al., 2017). Evidence here suggests that, in these low‐density mothers, embryos have higher expression of FoxO‐targeted genes and thus lower insulin‐signaling activity, which ultimately results in their primarily wingless adult phenotype. The opposite is true in aphid mothers that experience high densities. Research Highlights: Transcriptional profiling of winged‐ versus wingless‐destined pea aphid embryos implicated the importance of the insulin‐signaling portion of the FoxO pathway. No differences in size or stage were found in winged‐ versus wingless‐destined embryos. Together, these results raise the hypothesis that FoxO regulates morph development in a tissue‐specific manner.